Utilization of Integrated Community Case Management of Childhood Illnesses at Health Posts in Southern Ethiopia - Berhanu A; Alemayehu M; Daka K; Binu W; Suleiman M (Dove Medical Press, 2020)
Asefa Berhanu,1 Mihiretu Alemayehu,2 Kassa Daka,2 Wakgari Binu,2 Mohammed Suleiman3 1Wolaita Zone Health Department, Wolaita Sodo, Ethiopia; 2Wolaita Sodo University, College of Health Sciences and Medicine, School of Public Health, Wolaita Sodo, Ethiopia; 3Wolaita Sodo University, College of Health Sciences and Medicine, Department of Anesthesia, Wolaita Sodo, EthiopiaCorrespondence: Wakgari BinuWolaita Sodo University, College of Health Sciences and Medicine, School of Public Health, P.o. Box: 138, Wolaita Sodo, EthiopiaTel +251 910107704Email nubonsa@gmail.comPurpose: Even if strategic actions were undertaken to tackle common childhood illnesses, Ethiopia still stood as one of the six countries accounting for half of the global under-five deaths. So this study aimed to assess the utilization of integrated community case management during childhood illness at health posts in the study area.Methods: A community-based cross-sectional study was conducted using a multistage sampling technique that includes 633 sick under-five children with common childhood illnesses. The data was entered into EpiData 3.1 and exported to SPSS 20 for further analysis. Descriptive statistics, bivariate and multivariate logistic regression analyses were computed and adjusted odds ratio within 95% confidence interval was used to measure the statistical association between variables.Results: Out of the planned 633 participant, 624 caregivers underwent all the study components making the response rate 98.6%. The study indicated that only 10.6% of the sick children sought care from health posts. Income (AOR = 2.99, 95% CI: 1.37– 6.53), previous service utilization (AOR = 6.66, 95% CI: 1.81– 24.04), awareness of service availability (AOR = 4.74, 95% CI: 1.39– 12.10), ownership of health insurance (AOR = 2.63, 95% CI: 1.45– 4.76), distance (AOR = 5.23, 95% CI: 1.69– 10.19) and type of illness (AOR = 2.97, 95% CI: 1.41– 6.25) were the associated factors.Conclusion: The low utilization of integrated community case management insights to focus on availing additional well-equipped health posts, creating community awareness on services at health posts and at what time the services are given to address the problem of the majority.Keywords: ICCM, health post utilization, fever, diarrhea, cough, Kindo Didaye